PERAN KEMENTERIAN AGAMA DALAM MENANGANI KEKELIRUAN PENENTUAN ARAH KIBLAT KUBURAN DI KABUPATEN GOWA - Mujahidah, Wardatul; Alimuddin, Alimuddin (HISABUNA: Jurnal Ilmu Falak, 2025)
Determining the direction of the Qibla is an important aspect in the implementation of Islamic worship, both in prayer and in burial. Mistakes in determining the direction of the Qibla, especially in burials, can affect the solemnity and validity of worship procedures. In Gowa Regency, there are still a number of graves that do not face the Qibla correctly. This study aims to examine the factors causing the wrong direction of the Qibla of graves and to analyze the role of the Ministry of Religion of Gowa Regency in dealing with this problem. This type of research is field research with a qualitative approach, which is carried out through observation, interviews, and documentation. In addition, a sharia approach is used because it is related to Islamic law, as well as a falaky approach based on Islamic astronomy. The results of the study indicate that the wrong direction of the Qibla of graves is caused by limited measuring instruments, lack of public understanding of the importance of the correct direction of the Qibla, and geographical conditions that make measurement difficult. The Ministry of Religious Affairs of Gowa Regency has taken strategic steps such as socialization, re-measurement using the falakiyah method, and the use of modern technology to determine the direction of the qibla accurately. The implications of this study emphasize the importance of increasing public awareness of the direction of the qibla and the need for active involvement of the Ministry of Religious Affairs in standardizing the direction of the qibla in cemeteries. These efforts can be strengthened through ongoing counseling and the application of measuring instruments based on falakiyah technology Keywords: Qibla Direction, Ministry of Religion, Cemetery